Dampak Pengembangan Ekonomi Lokal melalui Community Based Tourism terhadap Kesejahteraan Ekonomi Masyarakat di Desa Tamansari, Banyuwangi, Jawa Timur - Harod Rahmad Novandi; Isbandi Rukminto Adi (Kementerian Koordinator Bidang Pembangunan Manusia dan Kebudayaan Republik Indonesia, 2021)
Tourism became an interesting and promising sector for development. World Travel and Tourism Council (2018) estimates that tourism contributes to up to 10.4% of global gross domestic product and 313 million jobs or 9.9% of global employment in 2017. Tamansari Village, Banyuwangi Regency, East Java Province, is exploited, which makes the village the spearhead of local economic drivers. This research discusses the impact of local economic development (LED) through community-based tourism (CBT) in Tamansari village, Banyuwangi Regency, Indonesia. The research area and using qualitative approach with descriptive research. While collecting data using in-depth interviews with 30 informants consisting of local government, local economic organizations, and local communities. The results of this research show a positive impact, the first impact of local economic development on work behavior, in the second impact of LED on Family Financial Management the conditions, The third impact of LED on the Improvement of the Family Economy, The fourth impact of local economic development on changes in mindset and behavior of stakeholders in the community. Based on this research's results and facts, the activities carried out have a more positive impact, where there is progress in the local economy mindset, the addition of new livelihoods, increased income, and financial management.